The Effect of the strategy PQ4R on the achievement of geography and the development of the knowledge skills of fourth grade students (Journal of the College of Basic Education, 2019)
This study aims at identifying the effect of the PQ4R strategy on the of achievement geography and the development of the knowledge skills of the fourth grade students. The sample consisted of( 67) students distributed in two groups with 32 students in the experimental group that studied geography using PQ4R and (35) students in the control group, which studied the same article in the traditional way, and then the researcher conducted the equivalence between the two groups in the variables (previous knowledge, intelligence test, the age of time calculated months), the researcher relied on two tools to measure the variables of the research, Collectible (48) The second tool represents the scale of the skill of knowledge beyond the knowledge developed by Kumar (1998), composed of (42) paragraph, the researcher confirmed their honesty, stability, and characteristics of psychometric, the study has reached the superiority of students in the experimental group on students Control group